2005
DOI: 10.1615/critrevimmunol.v25.i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th2 Lymphocytes in Autoimmune Disease

Abstract: This review reconsiders how the Th1/Th2 paradigm can be applied to Th1-mediated autoimmune disease. Although there is evidence that autoimmune diseases such as multiple sclerosis, type 1 insulin-dependent diabetes mellitus, and posterior uveitis are Th1 mediated and that in some cases reduction of the Th1 response or a Th2 type shift may alleviate disease, many apparent exceptions are now well documented. These exceptions center around the contradictory actions of the Th1 cytokine IFN-gamma and the evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 0 publications
1
72
0
4
Order By: Relevance
“…Immunity, which has the fundamental role to protect and defend the organism from the disease 16, 17, 18, is also involved in the homeostasis and health maintenance against autoimmunity diseases and tumors 17. The exacerbation of cytotoxic CD8+ T lymphocytes 18 and CD4+ T Helper 1 (T H 1) 19 responses were associated with inflammatory diseases and autoimmunity disorders 20. T H 1 activity is mainly based on the production of interferon‐gamma (IFN)‐γ, which optimizes the antimicrobial responses and fosters CD8+ T lymphocyte activity, and also appears to play a fundamental role in triggering autoimmune responses 21, 22, 23, 24, 25, 26, 27, 28, 29.…”
Section: Introductionmentioning
confidence: 99%
“…Immunity, which has the fundamental role to protect and defend the organism from the disease 16, 17, 18, is also involved in the homeostasis and health maintenance against autoimmunity diseases and tumors 17. The exacerbation of cytotoxic CD8+ T lymphocytes 18 and CD4+ T Helper 1 (T H 1) 19 responses were associated with inflammatory diseases and autoimmunity disorders 20. T H 1 activity is mainly based on the production of interferon‐gamma (IFN)‐γ, which optimizes the antimicrobial responses and fosters CD8+ T lymphocyte activity, and also appears to play a fundamental role in triggering autoimmune responses 21, 22, 23, 24, 25, 26, 27, 28, 29.…”
Section: Introductionmentioning
confidence: 99%
“…T cells are important players in normal immunity, but also play a critical role in the development and persistence of autoimmunity [7][8][9]. Clinical studies conducted on IVIgtreated patients have revealed significant modulations of T cell functions in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of such an immune response may benefit autoimmune diseases, but exacerbate chronic viral infections such as chronic HCV and HBV infections, because the balance of Th1/Th2 response is shifted toward Th1 in autoimmune reaction (Crane and Forrester, 2005;Afzali et al, 2007) and skewed toward Th2 in the immune response of chronic HBV and HCV infections (Bertoletti et al, 1997;Rossol et al, 1997;Tsai et al, 1997). The explanation for this scenario remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this scenario remains elusive. The Th1/Th2 imbalance is regarded as an integral part of the complex interactions in the development of autoimmune disease (Crane and Forrester, 2005), and this may also apply for viral infections with various characteristics (Bertoletti et al, 1997). Other pathophysiological processes possibly involved in the complex multifactorial genetic regulation and the action of vitamin D in the autoimmune and viral disorders may also be responsible for this scenario.…”
Section: Discussionmentioning
confidence: 99%